Ad&Art: Definition and practices of “outdoor artvertising” as a creative resource in urban planning: from physical to digital and NFT media - Elías-Zambrano, Rodrigo; Palomo-Domínguez, Isabel; Černikovaitė, Miglė Eleonora (Street Art & Urban Creativity, 2025)
Art functions as a communicative tool that enriches the broader communication system by transferring artistic principles to advertising campaigns and their audiences, thereby endowing promoted products with aesthetic and cultural qualities. In outdoor advertising and street-based formats, art permeates the urban environment, transforming the cityscape and engaging passers-by in everyday settings. This study analyses the effects of advertising art in public streets, considering it a vital element in the life of neighbourhoods and cities. It aims to illustrate different expressions of intertextuality between art and advertising within the contexts of urban planning and architecture, highlighting a strong relationship between commercial products and artistic works in public space. The methodology is based on a literature review as a valid analytical approach, examining how the concept of art has been incorporated into advertising campaigns. The results identify multiple conceptions and materializations of art-advertising intertextuality in urban landscapes.